Circulating plasma levels of miR-106b-5p predicts maximal performance in female and male elite kayakers - Torres-Aguilera, Irene; Pinto-Hernandez, Paola; Iglesias-Gutierrez, Eduardo; Terrados, Nicolas; Fernandez-Sanjurjo, Manuel (Frontiers in Sports and Active Living, 2023)
Introduction: Plasma miR-106b-5p levels have been described as an exercise performance predictor in male amateur runners, although no information is available about female athletes. The aim of this study was to analyse the predictive value on sports performance of plasma miR-106b-5p levels in elite female and male kayakers at the beginning and at the end of a training macrocycle, as well as the potential underlying molecular mechanisms using an in-silico approach. Materials and Methods: 8 elite male (26.2±3.6 y) and 7 elite women (17.4±0.5 y) kayakers from the Spanish national team. Two fasting blood samples were collected, starting point of the season (A) and maximum fitness level (B). Circulating plasma levels of miR-106b-5p were analysed by RT-qPCR. Maximal 500m performance was recorded at B. Results and Discussion: miR-106b-5p levels had no differences between A and B neither in women nor in men. In men but not in women, miR-106b-5p levels showed a negative significant correlation with performance in B which highlights its predictive value for performance. However, in women, progesterone emerged as a determinant and the ratio miR-106b-5p/progesterone showed a significant negative correlation with performance. In-silico analysis reveals potential targets in a number of genes of relevant to exercise. Conclusions: miR-106b-5p emerges as a biomarker of athletic performance in men and, in women if the menstrual cycle is considered. This highlights the need to analyse molecular response to exercise in men and women separately, and considering the stage of the menstrual cycle in women as a relevant factor.